Biopics as Postmodern Mythmaking - Cucca, Valentina (Academic Quarter | Akademisk kvarter, 2011)
Biopics as Postmodern Mythmaking by Valentina Cucca takes as its starting point the fact that the biographical genre has experienced a renewed prominence. The main goal of her article is to identify links and connections between many contemporary socio-cultural issues and the ways in which biopics are able to thematize and rework them. She also aims at explaining which have been and are the more or less intrinsic changes and trends of this genre, which have led to rank current productions under a label (biopic). Finally, Cucca aims at revealing to which extent biopics’ symbolical universes are able to thematize, reflect and rework social, political and cultural identity uncertainties that have invested postmodern subjectivities.